Modeling of Solar Photovoltaic Thermal Modules - Panchenko, V. (Springer Verlag, 2019)
In the presented article the technique of creation of three-dimensional models of solar photovoltaic thermal modules in the system of computer-aided design of Compass 3D is considered. The article also considers the method of visualization of the thermal mode of operation of the water radiator of the photovoltaic thermal concentrator solar module, the model of which was created in the automated design system. A technique for manufacturing a prototype of a solar tile shell manufactured using additive technologies is proposed. Â© 2019, Springer Nature Switzerland AG.